2001
DOI: 10.1080/026404101753113822
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between torque and joint angle during knee extension in boys and men

Abstract: The length-tension relationship of muscle contraction is well documented in adults. However, research on this relationship in children has been limited. The aim of this study was to compare differences in the torque-joint angle relationship of the quadriceps muscle in children and adults. Eight boys aged 8-10 years and eight men aged 20-26 years performed two maximal voluntary isometric contractions at six knee joint angles (20 degrees, 40 degrees, 60 degrees, 80 degrees, 90 degrees, 100 degrees). The mean of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 33 publications
3
45
2
Order By: Relevance
“…Although O'Brien et al [32] and Kluka et al [33] have shown no difference of optimal angle (i.e., the angle where force is maximal) between children and adults, Marginson and Eston [34] showed that the optimal angle corresponded to longer muscle lengths in children compared to adults. As all studies used the same angle to compare the fatigability between children and adults, their results could be affected since the children could exercise at a shorter relative length than adults.…”
Section: Musculo-tendinous Stiffnessmentioning
confidence: 99%
“…Although O'Brien et al [32] and Kluka et al [33] have shown no difference of optimal angle (i.e., the angle where force is maximal) between children and adults, Marginson and Eston [34] showed that the optimal angle corresponded to longer muscle lengths in children compared to adults. As all studies used the same angle to compare the fatigability between children and adults, their results could be affected since the children could exercise at a shorter relative length than adults.…”
Section: Musculo-tendinous Stiffnessmentioning
confidence: 99%
“…This angle was chosen as it represents the optimal vastii muscle length, i.e. the knee angle at which the maximal knee extension torque can be generated [19]. In addition, maximal voluntary activation is the greatest at this angle [20].…”
Section: (B) Assessment Of Neural Drive (I) Experimental Set-upmentioning
confidence: 99%
“…Afterwards, they would once again be positioned on the dynamometer chair, this time without the support of the quilt. The maximum isometric torque of the knee extension was evaluated using maximum voluntary isometric contraction (MVIC) at 80° of knee flexion, as suggested by Marginson and Eston 15 . Three MVICs were performed and the highest peak torque reached was maintained.…”
Section: Methodsmentioning
confidence: 99%